Konsep I'rab Dalam Pandangan Ibrahim Musthafa dan Ibrahim Anis - Hazuar Hazuar (Institut Agama Islam Negeri Curup, 2019)
There are some objectives on discussion of Irab concept in Ibrahim Mustafa and Ibrahim Anis perspectives. The mehod used in this research was Descriptive Analysis. In his book, Ihya al-Nahwi Ibrahim Mustafa explains that there are only two Irab; Dhammah and Kasrah. Dhammah functions as subject (Isnad), meanwhile Kasrah functions as majmu ( idhafah). He rejected fathah as irab because it is only lines which is seldom communicated by Arabians, and it doesnt infuence meaning for communication. On the contrary, irab concept as stated by Ibrahim Anis who declined that there were funtions of irab neither rules nor meaning. The findings of this reserch that irab concept stated by Ibrahim Mustafa and Ibrahim Anis was contrast. Irab concept used by Ibrahim is simillar to Ibnu Mada al-Qurtubi on which the changing of irab was caused of amil (actor) as it was used by experts of Nahwu traditionally. However, irab concept used by Ibrahim Anis rather the same as the thoughts of Nahwu Qutrub which is extremely used irab in ditermining a meaning. Then Ibrahim Anis view that the function of irab was result the experts of Nahwu.